Genetic analysis of LRRK2 variants in Han Chinese patients with Parkinson’s disease - Xinyue Deng; Xue Yan; Zhi Song; Wen Zheng; Hongbo Xu; Yan Yang; Jiangang Wang; Lamei Yuan; Hao Deng (PLoS ONE, 2026)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder, with variants in the leucine rich repeat kinase 2 gene ( LRRK2 ) being frequent genetic causes of inherited PD. This study aimed to screen for LRRK2 variants and assess their effects on PD susceptibility in the Han Chinese population. LRRK2 variants were identified through whole exome sequencing and confirmed by Sanger sequencing in 468 unrelated PD patients and 566 controls. The identified variants were analyzed via bioinformatics predictions and statistical analyses, by interpreting existing literature and database evidence. Twelve variants were detected, including p.A419V, p.P755L, p.I786F, p.C925Y, p.M968K, p.R1067Q, p.R1320S, p.I1339M, p.P1446L, p.D1756Y, p.H2206Y, and p.G2385R. Among participants, 14.74% of PD cases and 7.24% of controls carried at least one LRRK2 variant (odds ratio [OR]: 2.2144, 95% confidence interval [CI]: 1.4728–3.3294, P = 0.0001). The residues p.P755, p.R1067, p.R1320, p.P1446, and p.D1756 are comparatively conserved. The variants p.R1067Q and p.D1756Y, absent in controls, were predicted to be damaging. Compared to controls, PD patients had higher frequencies of p.A419V (OR: 4.2820, 95% CI: 1.4047–13.0530, P = 0.0054, corrected P = 0.0324) and p.G2385R (OR: 2.1149, 95% CI: 1.2682–3.5268, P = 0.0034, corrected P = 0.0324). These findings suggest that the LRRK2 variants, p.R1067Q and p.D1756Y, may act as likely pathogenic variants in PD, while p.A419V and p.G2385R might be risk factors for increased PD susceptibility in the Han Chinese population.